Fenômeno bullying : um estudo de caso sobre a violência simbólica no Colégio de Aplicação de Sergipe - Mendes, Gisele Millen (2010)
In the last years, news media and magazines of national coverage, constantly commentate on the bullying phenomenon. Bullying is a word from British origin, and it has no translation into Portuguese. It is a kind of violence that may happen among students of private as well as public schools, unleashed in a repeated form against one single and same victim along the time and within an instability of power, and it may cause irreparable psychological damages to psychism, to the personality, character and self - esteem of its victims, with consequences along all life. The phenomenon Bullying has been in practice for a long time at schools and is characterized as a symbolic and shrouded violence. As a matter of fact, students as well as educators have experienced it many times and don‟t know how to deal with it, mostly on prejudicing and disrespect situations to the others. No doubt the damages such problem cause to its victims, but it is necessary to make it clear that plays among students are not only important, but necessary to develop their identities and inter personal relations. The aim of this research is to understand if students suffer such problems on their dignities and if there is a demand to the recognition of the differences in CODAP Colégio de Aplicação , in Universidade Federal de Sergipe, at São Cristovão County-SE. It is a qualitative research, with some quantitative data, like data collection instruments that were used besides the literature review about the essay, questionnaires, with opened and closed questions for 82 students from the 6o. to the 9o. year of Fundamental Level, semi structured interviews with 14 teachers, Directors, Vice Directors, Pedagogical Supervisors, Phsycologists, Educational Orientators and general services workers of the school and observations of its common life. The majority of the teachers and students knew nothing about the subject, even though they thought the research was relevant to the school. For some interviewed teachers and office workers, the phenomenon bullying is practically non existing in the school; the plays, according to students‟ ages are the ones they refer to. 12 students were interviewed with the objective to clarify at what moment such plays turn into violence and which are the most common problems at school. As a result of the research, we can see that 62% of the interviewed students either were or are victims of some kind of prejudice in the researched school, but more than half of them don‟t bother with the annoyance and provocations. Such data demonstrate that it is necessary to go beyond the appearances of the results and take in consideration the students‟ perception related to the subject.